One belt one road initiative: a difficult way to the Chinese dream - Syzdykova, Zhibek; Suleymanova, Shukran; Nazarova, Helena; Mikhaylova, Natalia (Opción, 2019)
The purpose of the research is to identify the main internal and external problems that complicate China's global leadership. In the work, the methods of historical, political, comparative, system analysis were used to cover the interdisciplinary field of projecting a selected topic. As a result, in Central Asia, in particular, in Kazakhstan there may be a conflict between the strategic interests of China and Russia. It can be concluded that in the short term China will not become the only leader. There will be the difficulties on the path to China’s global leadership, at least in the next decade.